1984
DOI: 10.3382/ps.0630565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light and Feeding Space on Leg Abnormalities in Broilers

Abstract: The influence of two management factors on the incidence and severity of leg abnormalities was studied in three experiments utilizing a total of 7200 male broiler chickens. Birds provided intermittent illumination (IL) had significantly fewer and less severe leg abnormalities than birds under continuous illumination. Broilers given 2.94 cm of feeding space per bird had more but less severe leg defects than birds given 1.47 cm of feeding space. Bird activity was greater under IL and is deemed to be at least par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 4 publications
0
26
1
1
Order By: Relevance
“…This suggests that slower early growth rate may not be the only factor responsible for reduced skeletal disease. Broiler lighting programmes with periods of darkness, both of the increasing and intermittent type result in fewer leg abnormalities than continuous light (Buckland et al, 1973(Buckland et al, , 1976Simmons, 1982;Robbins et al, 1984;Wilson et al, 1984;Classen and Riddell, 1989). It is possible that metabolic changes occurring during darkness (Aschoff and Pohl, 1970;Aschoff and Saint Paul, 1976;Decuypere and Kuhn, 1984;Luijtelaar et al, 1987) may benefit skeletal growth.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This suggests that slower early growth rate may not be the only factor responsible for reduced skeletal disease. Broiler lighting programmes with periods of darkness, both of the increasing and intermittent type result in fewer leg abnormalities than continuous light (Buckland et al, 1973(Buckland et al, , 1976Simmons, 1982;Robbins et al, 1984;Wilson et al, 1984;Classen and Riddell, 1989). It is possible that metabolic changes occurring during darkness (Aschoff and Pohl, 1970;Aschoff and Saint Paul, 1976;Decuypere and Kuhn, 1984;Luijtelaar et al, 1987) may benefit skeletal growth.…”
Section: Discussionmentioning
confidence: 92%
“…Shorter day-length improves bird health and reduces stress but also results in slower growth rate than continuous light (Freeman et al, 1981;Robbins et al, 1984;Whitley et ah, 1984). Intermittent lighting programmes, which utilise repeated light and dark periods within a normal 24 h day have also been shown to improve bird health while maintaining equal or superior growth and food conversion to birds given continuous 22 H. L. CLASSEN, C. RIDDELL AND F. E. ROBINSON light (Buckland et al, 1971(Buckland et al, , 1973(Buckland et al, , 1976Ononiwu et al, 1979;Malone et al, 1980a, b;Wilson et al, 1984).…”
Section: Introductionmentioning
confidence: 96%
“…Simmons (1982) observed 17 lower incidence of twisted legs in chickens reared in intermittent light (IL) vs. continuous light (CL) and also that total daily bird activity, as measured by radar waves, was greater in IL than CL. Wilson et al (1984) found fewer and less severe leg abnormalities in IL vs. CL and stated that "birds given IL were much more active when the lights were on," whereas those provided CL were very docile. However, no quantitative data on activity were provided.…”
Section: Introductionmentioning
confidence: 95%
“…In growing boars, those subjected to enforced~exercise on a treadmill exhibited a lower incidence of leg ahnnrmalitiVs than controls (Perrin and BowlandJJ???). Simmons (1982) and Wilson et al (1984) postulated that effects of light treatments on the incidence of leg disorders in broilers jwere related to differences' in activity under the different treatments. Simmons (1982) observed 17 lower incidence of twisted legs in chickens reared in intermittent light (IL) vs. continuous light (CL) and also that total daily bird activity, as measured by radar waves, was greater in IL than CL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the most common commercial treatments for ascites reduction is feed restriction Arce et al, 1992;Acar et al, 1995;Balog et al, 2000a). Other management techniques used in an attempt to reduce ascites involve intermittent lightingyactivity programs (Buckland, 1975;Ononiwu et al, 1979;Simons, 1982;Wilson et al, 1984;Classen and Riddell, 1989;Renden et al, 1991;Balog et al, 1997). The intermittent lightingyactivity programs cause the broilers to engage in more non-feeding activity or cause them to refrain from all activity including eating, during intermittent time periods, which results in a decreased growth rate.…”
Section: Introductionmentioning
confidence: 97%